2009
DOI: 10.1073/pnas.0901181106
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofIRAK1as a risk gene with critical role in the pathogenesis of systemic lupus erythematosus

Abstract: A combined forward and reverse genetic approach was undertaken to test the candidacy of IRAK1 (interleukin-1 receptor associated kinase-1) as an X chromosome-encoded risk factor for systemic lupus erythematosus (SLE). In studying Ϸ5,000 subjects and healthy controls, 5 SNPs spanning the IRAK1 gene showed disease association (P values reaching 10 ؊10 , odds ratio >1.5) in both adult-and childhoodonset SLE, in 4 different ethnic groups, with a 4 SNP haplotype (GGGG) being strongly associated with the disease. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
152
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 220 publications
(158 citation statements)
references
References 35 publications
4
152
1
1
Order By: Relevance
“…IRAK1 deficiency in humans has not been described. Intriguingly, however, IRAK1 has recently been identified as a susceptibility allele in human systemic lupus erythematosus (SLE), with a four-single nucleotide polymorphism haplotype showing association with disease (9,10). SLE is characterized by the presence of immune complexes (ICs) formed by autoantibodies associated with self-DNA and RNA, increased serum IFN-a levels produced principally by plasmacytoid dendritic cells (pDCs), and an IFN-ainducible gene signature (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IRAK1 deficiency in humans has not been described. Intriguingly, however, IRAK1 has recently been identified as a susceptibility allele in human systemic lupus erythematosus (SLE), with a four-single nucleotide polymorphism haplotype showing association with disease (9,10). SLE is characterized by the presence of immune complexes (ICs) formed by autoantibodies associated with self-DNA and RNA, increased serum IFN-a levels produced principally by plasmacytoid dendritic cells (pDCs), and an IFN-ainducible gene signature (11,12).…”
mentioning
confidence: 99%
“…Studies in mouse autoimmune disease models have shown that ICs trigger activation of pDC and autoreactive B cells via TLR7/9 signaling pathways (12,17). IRAK1, being a key component of the TLR7/9 signaling cascade, participates in elaboration of lupus development as elucidated through the use of IRAK1-deficient mice crossed to SLE-prone mice (9).…”
mentioning
confidence: 99%
“…Sawalha's letter (1) questions our interpretation of the results reported in our recent article (2). Sawalha states ''because of high LD in this locus, both IRAK1 and MECP2 should be considered candidate associations, '' echoing what we have explicitly discussed in our article.…”
mentioning
(Expert classified)
“…Linkage disequilibrium (LD) among TYK2 SNPs was examined and no association was revealed with SLE therefore it was concluded that TYK2 is not a genetic risk factor for SLE in a Japanese population (Kyogoku, 2009). 15. Chromosome X 15.1 Interleukin-1 receptor-associated kinase 1/Methyl-CpG-binding Protein 2 locus (IRAK1/MECP2), Xq28 IRAK1, a serine-threonine protein kinase, regulates multiple pathways in both innate and adaptive immune responses by linking several immune-receptor-complexes to TNF receptor-associated factor 6 in mouse models of lupus, Irak1 is shown to regulate nuclear factor κB (NFκB) in TCR signaling and Toll/interleukin-1 receptor (TLR) activation, as well as the induction of IFN-and IFN-, (Jacob, 2009) implicating IRAK1 in SLE. In a study of four different ethnic groups, multiple SNPs within IRAK1 were associated with both adultonset and childhood-onset SLE (Jacob, 2009).…”
Section: Chromosome 19mentioning
confidence: 99%
“…Chromosome X 15.1 Interleukin-1 receptor-associated kinase 1/Methyl-CpG-binding Protein 2 locus (IRAK1/MECP2), Xq28 IRAK1, a serine-threonine protein kinase, regulates multiple pathways in both innate and adaptive immune responses by linking several immune-receptor-complexes to TNF receptor-associated factor 6 in mouse models of lupus, Irak1 is shown to regulate nuclear factor κB (NFκB) in TCR signaling and Toll/interleukin-1 receptor (TLR) activation, as well as the induction of IFN-and IFN-, (Jacob, 2009) implicating IRAK1 in SLE. In a study of four different ethnic groups, multiple SNPs within IRAK1 were associated with both adultonset and childhood-onset SLE (Jacob, 2009). The identified polymorphism C203S in IRAK1 is not in any known functional domain, therefore it was suggested that the association may actually be with its neighbor, methyl-CpG-binding protein 2 (MECP2).…”
Section: Chromosome 19mentioning
confidence: 99%